RESPONSIBILITY FOR RULING ON A DELIBERATELY UNFAIR COURT DECISION IN THE CONTEXT OF CRIMINAL LEGISLATION REFORM - Paliukh, Lidiia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to formulate proposals on the normative regulation of the material basis of criminal liability for the ruling on a deliberately unfair court decision. Research methods: dialectical method, which is the basis for the application of other research methods; methods of analysis, synthesis, deduction, induction, dogmatic, technical and legal, used in the analysis of the rule under Article 375 of the Criminal Code of Ukraine, which provided for liability of judge for the ruling on a deliberately unfair sentence, decision, ruling, resolution; the modeling method was used in the construction of the draft criminal law, which would establish responsibility for the ruling on a deliberately unfair court decision. Results: formulation of proposals to the Criminal Code of Ukraine (draft Criminal Code of Ukraine) to establish liability for n ruling on a deliberately unfair court decision. Discussion: the content of the concept of unfair court decision has been analyzed; a position was formulated on the expediency of using the terms «illegal», «unfounded» in the disposition of the relevant norm of the draft Criminal Code of Ukraine to denote a court decision, for the decision of which criminal liability should be provided. The author has been analyzed the compliance of the article of the draft Criminal Code of Ukraine, which provides for liability for ruling on a deliberately illegal and unfounded court decisions, to the principle of the rule of law (in particular, in its aspect as legal certainty), as well as to the principles of criminalization. On the basis of the conducted research the position on formulation of the disposition of the corresponding criminal law norm is expressed.